Procedural Conditions for Avoidance of the Contract for the International Sale of Goods - Zdravkovic, Uros (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
Avoidance of a contract is a unilateral declaration of will by one of the contracting parties which, if validly made, produces an effect on the contract by terminating it. The UN Convention on Contracts for the International Sale of Goods (Vienna Convention, hereinafter referred to as: the Convention) contains only one article that, through one concise sentence, regulates the procedural conditions for terminating the contract. According to the Article 26 of the Convention, the declaration of avoidance of the contract is effective only if the other party is informed about it. The Convention does not provide for automatic termination of the contract, regardless of whether the material legal conditions for avoidance have been met. Article 26 of the Convention stipulates that the contracting party must declare the termination of the contract and must notify the other party thereof. The purpose of the notice of avoidance is to inform the other contracting party of the status of the contract. In the absence of a notice, the declaration of avoidance shall have no effect.The party exercising the right to avoid the contract is not obliged to initiate appropriate court or arbitration proceedings in relation to that issue, although it certainly has the right to notify the other party of the avoidance through a lawsuit to the competent court or arbitration.Notice of avoidance may be given in any form. It must, however, contain a sufficient degree of clarity about the party's decision to no longer be bound by the contract and to consider the contract terminated. The notice of avoidance must be unconditional, final, express and unambiguous. Positions in practice and doctrine agree that such a statement can be given implicitly, through conclusive actions. It is important, however, that such a statement must be clear, unambiguous, explicit and unconditional, in order to create the belief in a reasonable person that the contract has been terminated.The Convention does not regulate the possibility of revoking the declaration of avoidance. In this regard, there are several opinions in the literature, but one should lean towards the one based on the fact that revocation is possible until the moment when the other contracting party receives the notice of avoidance of the contract.
Keywords: Law on International Sale of Goods; CISG; avoidance of contract; declaration of avoidance